Parental influences on screen time and weight status among preschool children from Brazil: a cross-sectional study - Widjane Sheila Ferreira Goncalves; Rebecca Byrne; Marcelo Tavares Viana; Stewart G. Trost (BMC, 2019)
Abstract Background Little is known about the influence of parental attributes and parental screen time behaviours on pre-schooler's screen time and weight status in low-to-middle income countries. The purpose of this study was to examine the relationships between parental screen time, parental self-efficacy to limit screen time, child screen time and child BMI in preschool-aged children in Brazil. Methods Three hundred eighteen parent-child dyads from Caruaru, Brazil completed a survey measuring sociodemographic data, weekday and weekend screen time, and parental self-efficacy for limiting screen time. Height and weight were measured and used to derive BMI and BMI percentile. Observed variable path analysis was used to evaluate the relationships between the parental and child variables. Results Analyses were conducted for screen time on weekdays and weekend days. Parental screen time was positively associated with child screen time, either directly (weekdays = β = 0.27, p < 0.001, weekends = β = 0.24, p < 0.001) or indirectly through reduced self-efficacy to limit child screen time (weekdays = β = − 0.15, p = 0.004, weekends = β = − 0.16, p = 0.004). After controlling for household income, parental occupation, and parental BMI, greater child screen time on weekends, not weekdays, was associated with higher child BMI percentile (β = 0.15, p = 0.006). Conclusions Parental screen time and self-efficacy to limit screen time are important influences on child screen time and weight status in pre-schoolers from Brazil. Reducing parental screen time and increasing parental confidence to limit screen time may be effective strategy to prevent overweight in Brazilian pre-schoolers.